Metodika určování hodnoty rodinných podniků v procesu nástupnictví - Režňáková, Mária; Karas,Michal; Srbová, Pavla; Pěta, Jan; Brychta, Karel (My University, 2022)
Východiskem tvorby metodiky jsou oceňovací metody běžně používané pro oceňování podniků. Tato metodika nabízí upřesnění a modifikaci aplikace standardně používaných oceňovacích metod, které vycházejí z poznatků získaných analýzou dat českých podniků a postihuje specifika malých a středních rodinných podniků v ČR. Z tohoto pohledu se jedná o originální přístup, který byl vytvořen řešiteli projektu, zdůvodněn odpovídajícími metodami statistického zpracování dat a průběžně předkládán k recenznímu řízení v rámci prezentací na vědeckých konferencích a v odborných článcích. Metodika představuje originální přístup i z hlediska mezinárodního: autorům není známá jiná publikovaná metodika, která by měřila specifičnost rodinných podniků a současně prokázala jejich vliv na výkonnost rodinných podniků, a faktor rodinnosti zakomponovala do procesu stanovení hodnoty rodinného podniku. V rámci řešení projektu byl vytvořen faktor rodinnosti, který umožňuje zakomponovat specifika rodinných podniků do oceňovacího modelu. Navíc byl odvozen model nákladů vlastního kapitálu pro malé a střední podniky, který je modifikací CAPM a vychází z dat českých MSP. Zohledňuje jednak oborová specifika českých podniků a současně výnosovou míru dosahovanou v ČR. Uživatelé mají k dispozici celkové beta koeficienty (beta total) pro jednotlivé obory NACE (v mnoha případech i podobory), které pro podmínky ČR zatím nebyly kvantifikovány a jejich využití je širší než jenom v rámci této metodiky. Metodika poskytuje jednak doporučení pro upřesnění vstupních parametrů při určování hodnoty podniku dle účelu ocenění a očekávaného vývoje podniku, jakož i informace o oborových hodnotách parametrů používaných při oceňování. Uživatelé, kteří se profesně nevěnují této problematice, mají možnost využít vytvořený software, který umožňuje zjednodušeně stanovit hodnotu rodinného podniku. Zjednodušení spočívá v tom, že nelze zohlednit všechna specifika každého subjektu, který může být oceňován, ale také v tom, že vstupní parametry jsou nastaveny zpravidla na základě minulého vývoje. Současně má uživatel možnost tyto parametry upravit dle znalosti situace v oceňovaném podniku. Tato metodika je certifikovaná u České společnosti pro jakost (číslo certifikátu M063/M/2022 ze dne 29.11.2022)

The methodology is based on valuation methods commonly used for valuation of companies. This methodology offers a refinement and modification of the application of standard valuation methods based on the knowledge obtained from the analysis of data of Czech enterprises and affects the specifics of small and medium-sized family businesses in the Czech Republic. From this perspective, it is an original approach, which was developed by the project researchers, justified by appropriate methods of statistical data processing and continuously submitted for review in presentations at scientific conferences and in professional articles. In the framework of the project, a family-friendliness factor has been developed, which allows the specificity of family businesses to be incorporated into the valuation model. In addition, a cost of equity model for small and medium-sized enterprises was derived, which is a modification of the CAPM and is based on data from Czech SMEs. It takes into account both the industry specifics of Czech enterprises and the rate of return achieved in the Czech Republic. Users have at their disposal total beta coefficients (beta total) for individual NACE industries (in many cases even sub-industries), which have not yet been quantified for the Czech Republic and their use is wider than just within the framework of this methodology. The methodology provides both recommendations for specifying input parameters in determining the value of a company according to the purpose of the valuation and the expected development of the company, as well as information on the industry values of the parameters used in the valuation. Users who are not professionally involved in this issue have the possibility to use the software developed, which allows to determine the value of a family business in a simplified way. The simplification lies in the fact that it is not possible to take into account all the specifics of each entity that may be valued, but also in the fact that the input parameters are generally set on the basis of past developments. At the same time, the user has the possibility to adjust these parameters according to the knowledge of the situation of the enterprise to be valued. The methodology is also an original approach from an international point of view: the authors are not aware of any other published methodology that measures the specificity of family businesses and at the same time demonstrates their influence on the performance of family businesses, and incorporates the family factor into the process of determining the value of a family business. This methodology is certified by the Czech Society for Quality (certificate number M063/M/2022 dated 29.11.2022)
Methodology for determining the value of family businesses in the succession process
Česká společnost pro jakost, č. certifikátu M063/M/2022
Keywords: specifika rodinných podniků, výkonnost podniků, metody určování hodnoty podniků, faktor rodinnosti, náklady kapitálu, účetní beta koeficient; specifics of family businesses, business performance, methods of determining business value, family factor, cost of capital, accounting beta coefficient